2017
DOI: 10.1002/fee.1518
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nature imagery on people in severely nature‐deprived environments

Abstract: An estimated 5.3 million Americans live or work in nature‐deprived venues such as prisons, homeless shelters, and mental hospitals. Such removal from nature can result in an “extinction of experience” that can further lead to disinterest or disaffection toward natural settings, or even biophobia (fear of the natural environment). People who infrequently – or never – spend time in nature will be deprived of the numerous physical and emotional benefits that contact with nature affords. We report on the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 26 publications
5
59
0
Order By: Relevance
“…The present study corroborates previous findings (Nadkarni et al 2017 andTurner, 2018), that nature contact engenders feelings of calm and wellbeing. The additional insights offered by ART demonstrate that two different kinds of nature contact -via green spaces, and via nature images -both enabled being away, extent and fascination, albeit in different ways.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The present study corroborates previous findings (Nadkarni et al 2017 andTurner, 2018), that nature contact engenders feelings of calm and wellbeing. The additional insights offered by ART demonstrate that two different kinds of nature contact -via green spaces, and via nature images -both enabled being away, extent and fascination, albeit in different ways.…”
Section: Resultssupporting
confidence: 93%
“…Despite the apposite nature of ART (noted by Söderlund and Newman 2017), this analytical framing has not been widely deployed in prisons, and relevant published studies of the potentially therapeutic effects of nature contact are scarce. Moore's 1981 paper reported fewer sickness calls made by prisoners with a view of nature from their cell, but since then knowledge about the impact of nature contact in prison had advanced relatively little until two recent and significant contributions by Nadkarni et al (2017) and Moran and Turner (2018). In framing their experimental study of the impact of viewing nature videos on solitary-confined prisoners in a US facility, Nadkarni et al (2017) differentiate between direct, indirect, and vicarious nature contact.…”
Section: Prison Environments and Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, for some groups of people, such 'virtual' or 'vicarious' interactions are important and can have positive impacts (e.g. [21,22]).…”
Section: Definitionmentioning
confidence: 99%
“…One noteworthy study found that prisoners in solitary confinement exhibited a 26% reduction in aggression when exposed to nature videos during a daily, 1-hour exercise period as compared to the control group (Nadkarni, Hasbach, Thys, Crockett, & Schnacker, 2017). An earlier study (Weinstein et al, 2015) found that increased exposure to nature resulted in more community cohesion and substantially lower crime rates.…”
Section: Entry Into the Nature And Health Movementmentioning
confidence: 99%